PERTUMBUHAN DAN HASIL PADI GOGO VARIETAS TONDANO PADA PEMBERIAN ZAT PENGATUR TUMBUH DAN PUPUK KALIUM - Bahar, Edward (E-Journal Sungkai, 2012)
Upland rice is the main food crop for the people of Indonesia in addition there are various regions inIndonesia which main food besides rice. Rice cultivation has long been cultivated intensification , but thebusiness can not increase crops. One attempt to do is the provision of plant growth regulators andpotassium fertilization. This study uses a randomized block design arranged in a factorial with 3replications per each treatment without growth regulators A0= not regulators, A1=atonik 1.00 cc/liter ofwater, A2 = hydrasil 2.00 cc/liter of water, A3 = 5 EC 1.00 cc/liter air. without KCl = B0 , B1 = KCl 50kg/ha, B2 = KCl 100 kg/ha, B3 = 150 kg KCl/ha. From the results of the study showed that administrationof growth regulators and potassium fertilizers showed significant response to the age at exit panicle,number of productive tillers per hill, age at maturity, number of grains per panicle and weight of 1000seeds.